Membangun Kecerdasan Finansial Dengan Matematika Keuangan - Handayani, Ajeng Tri; Tambunan, Nurma (Peneliti.net, 2023)
After IQ (Intellectual Quotient), EQ (Emotional Quotient) and SQ (Spiritual Quotient) now comes FQ (Financial Quotient) or commonly known as Financial Intelligence. Because one branch of economics that has grown significantly in recent years is financial planning or financial planning. In principle, good financial planning is easy and anyone can do it themselves. All you need to do is understand financial mathematics and know the available capital market and money market products. Understanding financial mathematics makes a person financially savvy and gives them the ability to develop their own financial plan.